An Infant with Neonatal Abstinence Syndrome in the Setting of Hydranencephaly - Deerwester, K. S.; Avidan, O.; Craig, A. K. (Journal of Pediatric Neurology, 2019)
An infant of 37 weeks' gestation was born with signs and symptoms of neonatal abstinence syndrome (NAS). Upon further investigation, he was found to have congenital hydranencephaly, a condition in which the forebrain is absent. In this case report, we explore the mechanisms of NAS and hydranencephaly, and why an infant without a forebrain can still experience NAS symptoms.
Keywords: brain; neonatal abstinence syndrome; hydranencephaly